1996
DOI: 10.1093/oxfordjournals.eurheartj.a014878
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlled radiofrequency catheter ablation of manifest accessory pathways

Abstract: Temperature-controlled radiofrequency ablation of manifest accessory pathways is highly effective and safe. The temperature response is faster and significantly higher in left-sided energy applications compared to right-sided pulses. Peak temperature levels measured at the electrode tip are significantly higher during effective than ineffective pulses. Sudden rises in impedance are not completely prevented during temperature-controlled radiofrequency ablation of accessory pathway, although no procedure-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Energy accumulated within the cortical bone can contribute to damaging adjacent soft tissue due to thermal redistribution (thermal conduction and blood flow mechanisms). Unwanted temperature elevations near pelvic bone are of particular concern for adjacent nerves, which have a high thermal sensitivity with low thermal dose thresholds for permanent or transient damage [48,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Energy accumulated within the cortical bone can contribute to damaging adjacent soft tissue due to thermal redistribution (thermal conduction and blood flow mechanisms). Unwanted temperature elevations near pelvic bone are of particular concern for adjacent nerves, which have a high thermal sensitivity with low thermal dose thresholds for permanent or transient damage [48,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in temperature occurs in a range that is used for temperature-controlled RF catheter ablation of cardiac accessory pathways and is probably capable of inducing tissue injury at the lead tips (36,37). In cases in which distant regions were imaged (ie, when the center of the region to be imaged was located 30 cm or farther from the center of the lead loop in the craniocaudal direction), the increase in temperature at the lead tip decreased distinctly, with a maximum value of 4.45°C at an SAR of 1.3 W/kg (Table 1).…”
Section: Mr Imaging-induced Heating Effectsmentioning
confidence: 99%
“…Two studies concerning temperature-controlled radiofrequency ablation of accessory pathways in humans 21,22 found that applications on the atrial side of the tricuspid annulus (high-flow site) had significantly higher power consumption and lower reached average tip temperature than applications under the mitral valve (low-flow site, because the electrode tip is sheltered by the mitral leaflet). This is consistent with our finding that applications in the apex (low-flow area) had higher reached temperature and lower power consumption.…”
Section: Ablation Sitementioning
confidence: 99%